Delegation beyond the nation-state - Leow, A (2015)
This research investigates support for delegation to international organisations using a framework derived from post-functionalist theory in the EU literature. This theory is extended such that economic interests and cosmopolitan identity are not only determinants of support for delegation, but also vary in importance, depending on the type of international organisation in question (i.e. peace-keeping vs. economic). Hypotheses are tested using data collected by the Chicago Council of Global Affairs (2007) and the 5th wave of the World Values Survey. The former also allows for a test of endogeneity - a persistent issue in the literature - using instrumental variables for an Indian sample.